Relationship between porosimetry measurement and soil-water characteristic curve for an unsaturated residual soil - Rahardjo, Harianto (2011)
Soil–water characteristic curve (SWCC) is an important tool for determining the engineering properties of unsaturated soil. This depends on the size and distribution of pore structures which control the permeability and amount of volume change. Mercury Intrusion Porosimetry tests can be used to determine the size, amount and distribution of pore spaces of the soil in a shorter time period compared to the pressure plate test. A soil-air characteristic curve (SACC) can be determined using the volumetric air content as measured in the Mercury Intrusion Porosimetry test. In this paper, SACC parameters are introduced. There appears to be a relationship between the soil-air characteristic curve and the soil-water characteristic curve of a soil. Relations between the SACC and the SWCC parameters are analysed in the light of unsaturated soil mechanics. The results indicate that the pore size distribution of a residual soil varies with depth due to differing degrees of weathering.